Menstrual hygiene: knowledge and practices during menstruation among adolescent girls in urban slums of Jorhat district, Assam, India - Das, Netri; Tasa, Anadi Swami (International Journal Of Community Medicine And Public Health, 2019)
Background: Menstruation is still clouded by taboos and socio-cultural restrictions resulting in adolescent girls remaining ignorant of the facts of menstruation and hygienic practices, which sometimes results in adverse health outcomes. The present study was carried out to assess the knowledge and practices regarding menstrual hygiene, to find out the disorders during menstruation and to determine the factors associated with existing practices of menstrual hygiene among adolescent girls Methods: A community-based cross-sectional study was conducted in two randomly selected urban slums of Jorhat district from March to August 2017 among 110 adolescent girls using predesigned pretested proforma. Data were analyzed using SPSS; association was determined using chi-square test with Yates correction or Fisher’s exact test, as appropriate. Results: 47.27% girls were aware about menstruation prior to menarche. Mother was the first informant in 65.38% of them. 69.09% were ignorant about the source of menstrual bleeding. Sanitary pads were used by 59.09% of girls. Majority (97.27%) practiced some form of restriction during menstruation. Dysmenorrhoea was the most common complaint (53.63%). Type of absorbent used was significantly associated with literacy status of girls and their mothers, socio-economic status, religion and prior knowledge about menstruation. Educational status of girls and their mothers were also significantly associated with satisfactory cleaning of external genitalia during menstruation. Conclusions: Ignorance and unsafe practices regarding menstruation, menstruation related problems and traditional beliefs and restrictions are quite common among adolescent girls in urban slums. Literacy status and awareness are the most important factors affecting the menstrual behaviours.